### 8 Answers

Relevance

- llafferLv 71 month agoFavourite answer
(8 - 5 ÷ 6) 6

as written, we divide first:

(8 - 5/6) 6

Now we subtract, so we'll need a common denominator:

(48/6 - 5/6) 6

(43/6) 6

Now multiply. the 6's cancel out:

43

- SumDudeLv 71 month ago
What operand symbol is in the place of my underline ... ")_6" AND THE ANSWER IS * (as in the times sign) ... and then the equation works.

- What do you think of the answers? You can sign in to give your opinion on the answer.
- billrussell42Lv 71 month ago
nothing to solve

(8-5 ÷ 6) 6

division has precedence

(8 – 5/6)5

(48/6 – 5/6)6

(43/6)6

43

so the equality is correct.

- micatkieLv 71 month ago
By distributive law:

(a - b) × c = a × c - b × c

Now, a = 8, b = 5 ÷ 6 and c = 6

Hence, (8 - 5 ÷ 6) × 6

= 8 × 6 - 5 ÷ 6 × 6

= 48 - 5

= 43

Still have questions? Get answers by asking now.